Laser Challenge of China (Global Journal of Science Frontier Research, 2022)
Preamble-Chinese President Xi Jinping, at a meeting with delegates of the People's Liberation Army of China (PLA) during the last session of the National People's Congress (NPC), demanded the introduction of scientific discoveries and innovative technologies in the army. Xi Jinping noted that new technologies are the key to modernizing the Armed Forces. The Chinese leader discussed with the military how to achieve the goals set in the field of national defense and army development and the implementation of the 13th five-year plan for the development of the armed forces. It is safe to say that laser weapons (LW) are on the agenda of China/1/.